2022
DOI: 10.3390/ijms23031828
|View full text |Cite
|
Sign up to set email alerts
|

A Pro-Inflammatory Signature Constitutively Activated in Monogenic Autoinflammatory Diseases

Abstract: Autoinflammatory diseases (AIDs) are disorders characterised by recurrent inflammatory episodes in charge of different organs with no apparent involvement of autoantibodies or antigen-specific T lymphocytes. Few common clinical features have been identified among all monogenic AIDs (mAIDs), while the search for a common molecular pattern is still ongoing. The aim of this study was to increase knowledge on the inflammatory pathways in the development of mAIDs in order to identify possible predictive or diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The efficacy of thalidomide in Blau syndrome was 50% in this study (Fig. 2 D), suggesting that more extensive inflammatory pathways or cytokines may be involved in the mechanism of Blau syndrome [ 22 ]. In addition, our cohort reported the efficacy of thalidomide after 1 year treatment of AGS, SAVI and TRAPS in clinical practice firstly [ 23 ].…”
Section: Discussionmentioning
confidence: 85%
“…The efficacy of thalidomide in Blau syndrome was 50% in this study (Fig. 2 D), suggesting that more extensive inflammatory pathways or cytokines may be involved in the mechanism of Blau syndrome [ 22 ]. In addition, our cohort reported the efficacy of thalidomide after 1 year treatment of AGS, SAVI and TRAPS in clinical practice firstly [ 23 ].…”
Section: Discussionmentioning
confidence: 85%
“…Studies have found that NF- κ B signaling pathway inhibition could promote the polarization of M2 macrophages and stimulate the activation of NF- κ B showing contrary effects [ 27 ]. In addition, MAPK is known to be a threonine/serine kinase that played a key role in inflammation by regulating NF- κ B-dependent gene transcription [ 28 ]. Previous studies have found that glucosamine might play an anti-inflammatory role by inhibiting the phosphorylation of MAPK protein which hinders the M1 polarization of local macrophages [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…While IL-1b potentiates responses of CD8 and various CD4 T cell lineages (19,21,23) it is mainly known to promote Th17 responses (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) as well as to induce IL-17producing gd T cells in mice (39). Interestingly, many autoinflammatory conditions, including FMF and gout, display upregulation of Th17-related cytokines (40)(41)(42). Not only IL-1b affects T cell responses, recent studies have shown that CD8 and CD4 T cells can in turn modulate the production of IL-1b in myeloid cells (43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%